ANALISIS PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP CORPORATE GOVERNANCE DISCLOSURE - Nirbhita, Nandana Antya; Adiwibawa, Agustinus Santosa (Diponegoro Journal of Accounting, 2015)
This study aims to Analyze the impact of a comprehensive set of corporate governance attributes (board composition, board size, director ownership, blockholder ownership, number of shareholders  and  number  of  audit  committee)  on  the  corporate  governance  disclosure  in Indonesia.  The  measurement  of  corporate  governance  disclosure  is  based  on  published  data created from a checklist item by United Nations.The samples used were selected by purposive sampling method and taken from list of LQ 45 on Indonesian Stock Exchange. There were 58 companies as samples. Observation period was 2011-2012, so the total number of sample used was 116 samples. Multiple regression was used to analyze the hypothesis.The  result  showed    that  number  of  shareholders  and  number  of  audit  committee  are positively significant affect corporate governance disclosure and director ownership is negatively significant affect corporate governance. Whereas board composition, board size, blockholder ownership have no effect on the corporate governance disclosure.